Profil Minat Belajar Siswa dengan Model Pembelajaran Problem Based Learning (PBL) pada Kelas XI - Saputri, Marina; Muliadi, Agus; Safnowandi, Safnowandi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
This study aims to determine students' interest in learning after being taught using the Problem Based Learning (PBL) learning model. This type of research is descriptive quantitative research using survey methods. Descriptive research is research that aims to describe the data systematically and factually, so that it can describe the state of the subject at that time. This research was conducted at MA Al-Ishlahul Ittihad Jabon Tentan, Bagu Village, Pringgarata District, Central Lombok Regency from March to May 2022, with a total of 20 respondents. In learning interest there are four indicators, namely: 1) feeling happy; 2) student involvement; 3) interest; and 4) students' attention. From the four indicators, a research instrument was formed in the form of a questionnaire with 20 positive statements. Then analyzed by the percentage formula for each item as a whole. Based on the results of the data analysis of the interest in learning questionnaire given to 20 respondents in class XI MA Al Islahul Ittihad Jabon Tentan, it can be concluded that students have an interest in learning with a high category of 12 students or 60%, while students' interest in learning in a very high category is 8 people students or 40%.